A novel approach to explore organochalcogen chemistry of tellurium based receptor for selective determination of silver ions in aqueous medium. (29th March 2017) - Bhasin, Aman K.K.; Singh, Jasminder; Singh, Harjit; Raj, Pushap; Singh, Narinder; Kaur, Navneet; Bhasin, K.K.
Graphical abstract: A novel tridentate receptor is developed for determination of Ag(I) in aqueous medium and environmental samples. Abstract: In due consideration of the growing importance of chemical sensors for the detection and quantification of toxic heavy metal ions to counter water pollution, a novel class of tellurium-based organic receptors has been investigated as a potentially sensitive and selective silver-ion probe in the present work. The new tellurium-incorporated Schiff base ligand (R1 ) was chemically synthesized and characterized using various spectroscopic techniques. Upon an exposure of organic nanoparticles (N1 ) of the title receptor ligand (R1 ) to a pool of select heavy metal ions, the former displayed high sensitivity and selectivity towards silver ions, in aqueous medium, with a detection limit of 2.34 nM. Interestingly, the presence of metal ions bearing close physico-chemical resemblance to silver exerted negligible interference in the ultra-sensitive detection of silver ions by the title probeN1 . Furthermore, the precision and accuracy of the potential silver-ion sensor (N1 ) in aqueous medium was established across a wide pH range as well as under saline conditions. The analytical utility of this potential silver-ion probeR1 was further investigated for real sample analysis of objects of environmental applicability. The results of the same were authenticated by using atomic absorption spectroscopy. In summary, an investigation into the utility of a new class of tellurium-based organic receptors as potential metal-ion sensors opens a new avenue into the rather poorly-comprehended environmental relevance of organotellurium chemistry.